Leadership–Motivation Asymmetry in Shaping OCB: Evidence from Public Sector Mediation Dynamics - Surianto, Surianto; Latief, Fitriani (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study aims to examine the effects of leadership style and work motivation on Organizational Citizenship Behavior (OCB), with job satisfaction as a mediating mechanism among civil servants. The study contributes by revealing an asymmetric mediation pattern in which leadership influences OCB both directly and through job satisfaction, while motivation operates primarily through a direct pathway without significant mediation. Using saturated sampling, data from 195 respondents were analyzed through inferential statistical techniques to test direct and indirect relationships. The results show that leadership significantly enhances job satisfaction and OCB, whereas motivation significantly affects OCB but not job satisfaction. Job satisfaction positively influences OCB and mediates only the leadership–OCB relationship. These findings highlight differentiated behavioral pathways, suggesting that leadership functions as a dual-impact driver, while motivation acts as an immediate trigger, with job satisfaction serving a selective reinforcing role in strengthening OCB.